Isocitrate protects DJ-1 null dopaminergic cells from oxidative stress through NADP+-dependent isocitrate dehydrogenase (IDH). - Yang, J.; Kim, M.J.; Yoon, W.; Kim, E.Y.; Kim, H.; Lee, Y.; Min, B.; Kang, K.S.; Son, J.H.; Park, H.T.; Chung, J.; Koh, H. (PLoS Genetics, 2017)
DJ-1 is one of the causative genes for early onset familiar Parkinson's disease (PD) and is also considered to influence the pathogenesis of sporadic PD. DJ-1 has various physiological functions which converge on controlling intracellular reactive oxygen species (ROS) levels. In RNA-sequencing analyses searching for novel anti-oxidant genes downstream of DJ-1, a gene encoding NADP+-dependent isocitrate dehydrogenase (IDH), which converts isocitrate into ?-ketoglutarate, was detected. Loss of IDH induced hyper-sensitivity to oxidative stress accompanying age-dependent mitochondrial defects and dopaminergic (DA) neuron degeneration in Drosophila, indicating its critical roles in maintaining mitochondrial integrity and DA neuron survival. Further genetic analysis suggested that DJ-1 controls IDH gene expression through nuclear factor-E2-related factor2 (Nrf2). Using Drosophila and mammalian DA models, we found that IDH suppresses intracellular and mitochondrial ROS level and subsequent DA neuron loss downstream of DJ-1. Consistently, trimethyl isocitrate (TIC), a cell permeable isocitrate, protected mammalian DJ-1 null DA cells from oxidative stress in an IDH-dependent manner. These results suggest that isocitrate and its derivatives are novel treatments for PD associated with DJ-1 dysfunction.